Synthesis and characterization of Al2O3 nanoparticles using sol gel method by chelating extracts of starfruit (Averrhoa bilimbi) for nanofluid applications - Kharisma Marta Judenta; Ratnawulan Ratnawulan; Gustaman Syarif (Department of Physics – Universitas Negeri Padang UNP, 2017)
Nanofluid has better thermal characteristics and better heat transfer coefficient compared to conventional coolant fluid [6].This makes the nanofluids has potential as a good alternative coolant fluid compared conventional coolant fluid. Nanofluids are a mixture of basic fluids such as water with solid particles of size 1-100 nm (Nanoparticles). In this study the nanoparticles to be used are Al2O3. The synthesis of Al2O3 was conducted by sol gel using chelation of Averrhoa bilimbi with calcination temperature of 1100 for 3 hours. Al2O3 powder obtained then characterized by using XRD. Furthermore, Al2O3 nanoparticles mixed into 100 ml of distilled water with concentration variations 0,2%; 0,5% dan 0,8% and characterized using test equipment Viscosity, Zeta Potential meter and Critical Heat Flux (CHF). Results obtained in the study was the effect of the addition of Averrhoa bilimbi extract as chelating against nanoparticles of Al2O3 to prevent agglomeration/buildup on each other. XRD data showed that the Al2O3 nanoparticles has crystallite size of 10,40 nm. Then the effect of addition Al2O3 nanoparticle concentration that were suspended in 100 ml of distilled water to the value of fluid Viscosity, Zeta Potential and Critical Heat Flux.Viscosity increases with the addition of Al2O3 nanoparticle concentration, at the same temperature (27°C) of optimum viscosity value at 0.8% concentration of 0.9830 mPa.s. Meanwhile, the potential zeta value also increases with the addition of Al2O3 nanoparticle concentration. The zeta potential value is optimum at 0.8% concentration of 35 mV. Furthermore the value of CHF at a concentration of 0.2%; 0.5% and 0.8% were 17.29%; 77.04% and 76.70% for each. Overall the value of CHF increases with the addition of Al2O3 nanoparticle concentration